Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Konsumen Baby SPA Di Aleankabut Hoz Kota Depok - Shovilia Shovilia; Eddy Hermawan Hasudungan Panjaitan; Nurwulan Kusuma Devi (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of service quality and promotion on customer satisfaction at Aleankabut Hoz baby spa in Depok City. A quantitative approach was applied, with data collected via questionnaires from 108 respondents. Multiple linear regression analysis was used. The results showed that both service quality and promotion had significant partial and simultaneous effects on customer satisfaction. Promotion emerged as the dominant variable influencing satisfaction, particularly through public relations and digital media strategies. The coefficient of determination (R²) of 89.2% indicates that the independent variables significantly explain the variation in customer satisfaction. The findings imply that enhancing empathy-based service quality and optimizing digital promotion strategies can increase customer loyalty in the baby spa sector.